Analisis Manajemen Kinerja KPK dalam Optimalisasi Pemulihan Kerugian Negara (Komisi Pemberantasan Korupsi, 2022)
The achievement of recovery of state losses due to the performance of the Corruption Eradication Commission (KPK) is considered not optimal, which indicates a problem in its performance management. Therefore, this research aims to find a micro (organizational) strategy for optimizing the recovery of state losses using the Balanced Score Card model. The problem of recovering state losses at the Corruption Eradication Commission will be analyzed using general policy theory, specifically the balanced scorecard (BSC) performance management theory and asset recovery theory. Overall, the balanced scorecard in measuring the performance of the Corruption Eradication Commission in recovering state losses due to corruption is still said to be sufficient, with a total score of 73%, meaning that KPK cannot achieve a balance between one perspective and another. In the qualitative analysis, the factors that influence the optimization of loss recovery are (1) the regulations applied are not optimal, especially in determining the penalties and fines obtained by the suspect; (2) Case arrears and less in terms of quality and quantity of cases investigated; (3) The quantity and quality of Human Resources are still low; 4) Synergy between the Corruption Eradication Commission and other Law Enforcement Apparatuses, which are still colliding with ego-sectoral conflicts.